2018
DOI: 10.1042/bsr20171193
|View full text |Cite
|
Sign up to set email alerts
|

The pseudogene-derived long non-coding RNA SFTA1P suppresses cell proliferation, migration, and invasion in gastric cancer

Abstract: Pseudogenes were once regarded as transcriptionally inactive and without specific molecular function. However, current evidence shows that pseudogene-derived long non-coding RNAs (lncRNAs) may be crucial regulators of human cancer development, including gastric cancer (GC). In the present study, we report that a pseudogene-derived lncRNA named surfactant associated 1, pseudogene (SFTA1P), which is 693-nt long, was significantly down-regulated in GC tissues compared with that in the adjacent normal tissues. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…In lung cancer, SFTA1P was down-regulated, which could induce upregulation of hnRNP-U-GADD45A followed by promotion of apoptosis and increasing of cisplatin chemosensitivity [34]. Besides, Zhang et al also found that SFTA1P could suppress lung adenocarcinoma cell migration and invasion [35] and similar functions were identified in gastric cancer [36]. That our study provide contradictory results may be due to the types of cancer in study, which warrants further studies to validate the rrole of SFTA1P in CRC.…”
Section: Discussionmentioning
confidence: 91%
“…In lung cancer, SFTA1P was down-regulated, which could induce upregulation of hnRNP-U-GADD45A followed by promotion of apoptosis and increasing of cisplatin chemosensitivity [34]. Besides, Zhang et al also found that SFTA1P could suppress lung adenocarcinoma cell migration and invasion [35] and similar functions were identified in gastric cancer [36]. That our study provide contradictory results may be due to the types of cancer in study, which warrants further studies to validate the rrole of SFTA1P in CRC.…”
Section: Discussionmentioning
confidence: 91%
“…Apart from PTENP1, some pseudogene-derived lncRNAs were also demonstrated to be downregulated in gastric cancer and play tumor suppressive roles in gastric cancer progression. SFTA1P, which is 693 nt long, was obviously decreased in gastric cancer tissues compared with the adjacent normal tissues (Ma H. et al, 2018). Increased expression of SFTA1P suppressed proliferation, migration and invasion of gastric cancer by partially inhibiting p53 signaling.…”
Section: Gastric Cancermentioning
confidence: 88%
“…SFTA1P were regarded as a tumor suppressor. Down-regulation of SFTA1P may be associated with decreased TP53 expression 47 . LncRNA SNHG1 promoted non-small cell lung cancer progression 48 .…”
Section: Discussionmentioning
confidence: 99%